Awareness of child oral health among parents and caregivers attending Pediatrics OPD at BPKIHS, Dharan - Shrestha, Sneha; Koirala, Bandana; Shah, Gauri Shankar; Kumar, Abhishek; Baral, Dharanidhar (Birat Journal of Health Sciences, 2022)
Introduction: Parents and caregivers are the key sources responsible for their children’s good health. They are the basic needs-provider and role models as well for their children to learn good oral habits early on. Thus, their awareness about the factors affecting child oral health is an essential component for the well-being of the child.Objectives: To assess awareness of child oral health among parents and caregivers attending Pediatrics OPD at BPKIHS, Dharan.Methodology: A cross-sectional questionnaire-based study was conducted among conveniently selected 400 parents and caregivers of six months-to-14-year-old children attending Pediatrics OPD, BPKIHS, Dharan. A single interviewer administered pre-tested standardized questionnaires to the participants. The questionnaires consisted of five domains: socio-demographic profile of the participants; child’s oral hygiene practices; child’s feeding and dietary habits; awareness of child’s first dental visit and presence of family dental problems; and child’s dental service utilization. Data were entered in MS excel 2007 and statistically analyzed using SPSS version 11.5. Data analysis included descriptive statistics.Results: Majority (90%) of the parents and caregivers were literate and 44.3% belonged to the lower-class socioeconomic status. 83.3% of the participants reported that their children took a sugary diet and 77.6% of them brushed once daily before breakfast. 91% of the respondents reported the age of the child’s first dental visit to be any age when there was a dental problem. The awareness of the presence of oral health problems in their child was seen in 29.5%, whereas 18% had made previous dental visits.Conclusion: Despite the fact that most parents and caregivers reported factors affecting their children's oral health, there was evidence of lack of awareness and, as a result, low utilization of dental services for their children.